2010
DOI: 10.1186/cc9280
|View full text |Cite
|
Sign up to set email alerts
|

Continuous glucose monitors prove highly accurate in critically ill children

Abstract: IntroductionHyperglycemia is associated with increased morbidity and mortality in critically ill patients and strict glycemic control has become standard care for adults. Recent studies have questioned the optimal targets for such management and reported increased rates of iatrogenic hypoglycemia in both critically ill children and adults. The ability to provide accurate, real-time continuous glucose monitoring would improve the efficacy and safety of this practice in critically ill patients. The aim of our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 36 publications
4
42
0
1
Order By: Relevance
“…The delivery of TGC may be further improved by the use of continuous glucose monitoring systems, 72 including those with paediatric decision support.…”
Section: Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…The delivery of TGC may be further improved by the use of continuous glucose monitoring systems, 72 including those with paediatric decision support.…”
Section: Strengthsmentioning
confidence: 99%
“…If a policy of TGC is to be recommended for children admitted to PICUs for reasons other than cardiac surgery, research is needed to further refine clinical algorithms for the delivery of TGC, and to assess whether or not delivery of TGC may be further improved by the use of continuous glucose monitoring systems, 72 including those with paediatric decision support.…”
Section: Recommendations For Further Researchmentioning
confidence: 99%
“…The utilization of CGM, currently being introduced slowly in paediatric intensive care units of developed countries [82,83], may help improve our understanding of the real burden and associated pathophysiology of childhood hypoglycaemia. As malaria seldom occurs in developed countries, we need to bring this technology to endemic areas.…”
Section: Hypoglycaemiamentioning
confidence: 99%
“…48 Using statistical definitions (Bland-Altman and Clarke error grid analysis) both this study and another demonstrated clinically acceptable correlation despite the aforementioned limitations. 49 There is sufficient trust in the technology that the 2017 HALF-PINT study investigating tight glycemic control in critically ill children used CGM to signal impending hypoglycemia. 50 …”
Section: Critical Illnessmentioning
confidence: 99%